Effect of intercrops on growth and yield of turmeric (Curcuma longa L.) - Hemalatha, R Chitra, P (Journal of Spices and Aromatic Crops, 2017)
The initial growth of turmeric is rather slow and takes about 4-5 months to cover the inter space. Therefore, the available space between the rows of turmeric could be effectively utilized by growing short duration crops like, vegetables, cereals etc. Hence, it is worthwhile to explore the possibilities of growing compatible crops with turmeric. With this background the experiment on effect of intercrops on growth and yield of turmeric was conducted at Agricultural Research Station, Bhavanisagar. Among the different intercrops, turmeric with cowpea recorded the maximum fresh rhizome yield per hectare (30.78 t ha-1) while turmeric + bhendi registered the maximum B:C ratio (2.68:1). Monocropping of turmeric recorded the lowest B:C ratio (1.67:1) among all the treatments.